The Relevance Of The Law Of Usury And Bank Interest In The Perspective Of Wahbah Az-Zuhaili - Pranoto, Ahmad Hadi; Nisa, Nafidatun; Assharofi, Faiz Abdul Majid; Savana, Oseolla; Lutfiyah, Lutfiyah (Jurnal Ilmiah Al-Hadi, 2025)
This article discusses the relevance of riba and bank interest from the perspective of Wahbah Az-Zuhaili. The approach used in this study is a qualitative approach, and the type of research is literature research. This research combines data collection techniques with document studies, so that data in the form of journals and books related to the thought of Wahbah Az-Zuhaili is used as a primary source in this study and refers to the work of Ibn Khaldun. The data used are related to Wahbah Az-Zuhaili's thoughts on the law of riba and the relevance between bank interest and usury. This research shows that, Wahbah Az-Zuhaili argues that bank interest is included in riba nasiah, which is prohibited because it is an addition to financial transactions without clear rewards and is only based on a delay in payment time. Wahbah Az-Zuhaili emphasized that bank interest is the same as jahiliyah usury, both large and small, and has been declared haram based on the Qur'an, Sunnah, and ijma' of the Companions. This practice is considered to be detrimental to borrowers and creates economic injustice.